HUBUNGAN TINGKAT PENGETAHUAN TIDUR DAN AKTIVITAS FISIK DENGAN KUALITAS TIDUR MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA TAHUN 2022 - Amelia Rahmawati (2022)
The survey results conducted by AIA show that Indonesian people who want to have 7-8 hours of sleep can only achieve 6 hours every day due to their increasing daily activities. Lack of sleep knowledge and physical inactivity can cause a person to have poor sleep quality. This study aimed to determine the relationship between sleep knowledge level and physical activity with sleep quality of students of the Faculty of Health Sciences UPN Veteran Jakarta in 2022. This study used a cross-sectional design with a proportional stratified random sampling technique. Research data collection is done through Google Form. The research instrument used was a sleep knowledge questionnaire, IPAQ-SF, and PSQI. This study used univariate and bivariate analysis with the Chi-Square test. The results showed that there was a relationship between sleep knowledge level (p = 0.011) POR value = 2,307 (95% CI: 1,318-4,039) and physical activity (p = 0.018) POR value = 1,777 (95% CI: 1,019-3,098) with student sleep quality. However, there was no relationship between age (p = 0.067) and gender (p = 0.197) with student sleep quality. Therefore, students are expected to increase their knowledge of sleep and be physically active to improve their sleep quality. Keywords: Physical Activity, Sleep Knowledge, Sleep Quality